Policing Legitimacy: Social Media, Scandal and Sexual Citizenship - Ellis, Justin R. (Crime and Justice in Digital Society, 2021)
Chapter 1. Exposing police transgression from below -- Chapter 2. The rules of digital media engagement -- Chapter 3. Making meaning of police use of force -- Chapter 4. Negotiating police legitimacy in the digital society -- Chapter 5. The limits of exposure on police accountability -- Chapter 6. The social media test -- Chapter 7. An unpredictable digital future.